(untitled) (Research, Society and Development, 2021)
Objective: To address the magnitude and associated factors of intimate partner violence against women in the COVID-19 pandemic. Methodology: This is an integrative literature review, performed by searching the MEDLINE database, using the descriptors “violence”, “woman” and “COVID-19”, associated with the Boolean operator AND. Studies available in full were included, published in the time frame covering the period of March/2020 and April/2021 and in Portuguese, English and Spanish, resulting in a sample of 10 articles. Results: From the selected sample, it could be seen that the COVID-19 pandemic increased the frequency and severity of violent acts committed by the intimate partner against women, with psychological, physical and sexual violence being the most reported types For them. Furthermore, the pandemic period triggered the emergence of new forms of abuse. The increase in time with the abuser at home, economic factors and the interruption or difficulty in accessing support services were identified as the main factors responsible for the occurrence and/or worsening of violence perpetrated by an intimate partner against women during the COVID-19 pandemic. Conclusion: Information regarding the magnitude and factors associated with intimate partner violence against women during the pandemic may help to develop strategies to prevent / combat the occurrence of this type of violence, in addition to contributing to the planning of actions to ensure assistance of women in other similar emergency situations.